(−)-Epigallocatechin gallate (EGCG) pharmacokinetics and molecular interactions towards amelioration of hyperglycemia, hyperlipidemia associated hepatorenal oxidative injury in alloxan induced diabetic mice. (1st December 2022) - Soussi, Ahlem; Gargouri, Manel; Magné, Christian; Ben-Nasr, Hmed; Kausar, Mohd Adnan; Siddiqui, Arif J.; Saeed, Mohd; Snoussi, Mejdi; Adnan, Mohd; El-Feki, Abdelfattah; Chappard, Daniel; Badraoui, Riadh
Abstract: Diabetes mellitus has become a serious problem associated with health complications, such as metabolism disorders and liver-kidney dysfunction. The inadequacies associated with conventional medicines have led to a determined search for alternative natural therapeutic agents. The present study was conducted to evaluate the hypoglycemic, antilipidemic, and antioxidant effects of EGCG in surviving diabetic mice. Alloxan diabetic mice were treated with EGCG. Their bloods were collected and submitted to various biochemical measurements, including blood glucose, cholesterol, triglycerides, urea, creatinine, and transaminases. Their livers and kidneys were isolated to assess oxidative damage and to perform histological analysis. Both EGCG and insulin treatment of diabetic mice resulted in a significant reduction in fasting blood glucose levels. EGCG supplementation also ameliorated hepatic as well as renal toxicity indices. Moreover, diabetic mice injected with EGCG exhibited significant changes in antioxidant enzyme activities in the liver and kidney. Histological analyses also showed that it exerted an ameliorative action on these organs and efficiently protected the liver-kidney functions of diabetic mice. EGCG was found to bind α-amylase, PTP1B, and α-glucosidase with good affinities ranging from −6.1 to −8.4 kcal/mol. The findings revealed that EGCG administration induced attractive curative effects on diabetic mice, particularly in terms of liver-kidney function. EGCG can, therefore, be considered as a potential strong candidate for future applications to treat and alleviate diabetic burden. Its pharmacokinetics, high affinities, and molecular interactions with the targeted receptors satisfactory explain the in vivo findings. Highlights: Alloxan diabetic mice exhibited glycemic, lipidemic and antioxidant disruptions. (−)-Epigallocatechin gallate (EGCG) treatment reduced glucose level. EGCG possessed good oral bioavailability and pharmacokinetic properties. EGCG ameliorated kidney and liver functions in diabetic mice. EGCG beneficial effects included interactions with α-amylase, PTP1B, and α-glucosidase.